Comparisons of macrofaunal communities occupying shores across the full particle-size spectrum reveals pebble beaches to be a distinct coastal habitat type. Issue 4 (2nd October 2022) - Robbins, A; Griffiths, CL; Nefdt, L
Abstract : Intertidal research has focused primarily on very fine to coarse sandy beaches (grain size <1 mm) and on rocky shores, while shores with grain sizes of 1-256+ mm have rarely been studied. Within South Africa, few published accounts describe the biota of very coarse sand (1-<2 mm), granule (2-<4 mm), pebble (4-<64 mm) or cobble (64-<256 mm) shores, and only one reports on boulder (256+ mm) shores. The objective here was to determine how many distinct habitat types occur across the full spectrum of particle sizes within this region, and what taxa characterise the biota of each habitat type. Biota from 14 shores of grain sizes 1-256 mm within the Western Cape Province (southeastern Atlantic Ocean) were sampled and compared with similar published data from 32 other regional sites with either finer or coarser grain size. Three main groupings emerged from a similarity analysis: sandy shores (of particle size <1 mm); pebble (4-<64 mm) shores; and boulder (256+ mm) plus rocky shores, with cobbles serving as a transition between those two. Sandy shores were characterised by various burrowing taxa, and boulder (>256 mm) and rocky shores mostly by grazing gastropods. Shores of 4-<64 mm particle grain size were colonised by a distinctive but previously unrecognised macrofaunal community characterised by an impoverished fauna dominated by small, mobile, mostly air-breathing arthropod taxa.